Reliability analysis of wireless communication equipment based on model selection - SUN Jin, HU Jicheng, JIAO Yaqi, WANG Kun (Zhihui kongzhi yu fangzhen)
The research of equipment failure distribution is the basis of reliability engineering. In view of the complex structure and failure mechanism of wireless communication equipment, numerous failure distribution types, difficulty in selecting and evaluating reliability models and other problems, this paper starts from the research on equipment failure distribution at the bottom level, takes typical wireless communication system vehicle self-organizing network equipment as the research object, and compares and analyzes the correlation coefficients and error values of equipment life exponential distribution, lognormal distribution and two-parameter Weibull distribution. By introducing the information criterion and the special goodness of fit test to analyze the fitting effect of the reliability model, the reliability analysis method of wireless communication equipment based on model selection is proposed, and the test and analysis are combined with actual cases to improve the accuracy and effectiveness of model selection.